EVALUATION OF NATURAL POTENTIAL AND VULNERABILITY OF TERRITORY TO RISKS. Case Study: Sântimbru Commune, Alba County (PANGEEA, 2025)
In a world in constant chaotic development, a study focused on a well established territory, with a detailed description of the existing situation and a correct analysis of the vulnerabilities resulting from the interactions between the natural and the anthropic component, with emphasis on providing solutions for restoring optimal functionality is imperative. This study seeks to identify, on the basis of a detailed analysis of the specificity elements, the inadequacies that arise from interactions between the natural environment and its anthropic use, and propose remedies and optimization of territorial functionality on medium and long term.
Keywords: natural potential; risk processes; vulnerability; GIS; raster interpolation